EXPERIMENTAL TOXICOLOGY IN SILICO - Tichy, Milon (Biomedical papers, 2005)
A review on applicability of in silico methods for toxicity testing by calculation for regulatory purposes, their survey and background of QSAR (Quantitative Structure-Activity Relationships) analysis are presented.
Keywords: Toxicity Testing/In Silico Methods/QSAR/Validation of Computer Models